What Does it Take to Become a Top-Swimmer? : Perceptions of Success Factors in Finnish Swimming - Kurki, Laura (2020)
The purpose of this Master’s thesis is to examine different factors that affect the possibilities of Finnish swimmers to succeed at the international level. This thesis focuses on the social, environmental, and organizational factors that influence athletes’ success. As a framework, the SPLISS (Sport Policy Factors Leading to International Sporting Success) model 2.0 and its nine pillars were used. The data of this study consisted of theme interviews of five individuals who are closely involved with top-level swimming in Finland. All the participants had different perspectives and backgrounds related to swimming. Two of the participants were competitive swimmers, out of which one has already achieved international success, while the other has not yet reached the international level. The other three participants were a swimming coach, a Finnish federation official, and a former physical education lecturer as well as swimming expert. The participants were asked to rank the nine SPLISS pillars from least important to most important, according to their own perspective. All the interview themes were derived from the nine pillars. The results reveal that all the nine pillars were seen as important for the swimmers in order to succeed internationally. Two pillars scored a bit higher than the others. Pillars seven and three, which stand for coaching provision and coach development, alongside foundation and participation scored higher than the other pillars, respectively. All the pillars were seen as important in some phase of the swimmer’s career. Coach provision and coach development was one of the factors with the highest need of improvement in Finnish swimming.